2007
DOI: 10.1073/pnas.0705240104
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral deletion of mature alloreactive B cells induced by costimulation blockade

Abstract: (4). In animal models, the major evidence comes from studies using the MT mice. These mice have a targeted mutation at the transmembrane domain of B cell receptor -chain and have defects in B cells and antibody secretion (5), as well as a reduction in T cell and dendritic cell numbers (6). In a mouse cardiac transplant model in which B10.A (H-2 a ) hearts are transplanted into H-2 b MT mouse, acute rejection is prevented. Passive transfer of complement-activating alloantibodies restores acute rejection, sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 44 publications
1
22
0
Order By: Relevance
“…We interpret these observations as consistent with our recent report that alloreactive B cells are deleted in tolerant recipients (20). In those studies using 3-83 Igi mice as recipients of C57BL/6 heart grafts, we observed that the deletion of alloreactive B cells was at the mature B cell stage.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…We interpret these observations as consistent with our recent report that alloreactive B cells are deleted in tolerant recipients (20). In those studies using 3-83 Igi mice as recipients of C57BL/6 heart grafts, we observed that the deletion of alloreactive B cells was at the mature B cell stage.…”
Section: Discussionsupporting
confidence: 82%
“…Surprisingly, depletion of CD25 ϩ cells from the tolerant spleen did not result in a statistically significant increase in allo-IgG titers ( p Ͼ 0.05), despite a restoration of allograft rejection. We hypothesized that this is due to alloreactive B cells being deleted in the periphery of tolerant mice (20) and reasoned that removal of the regulatory T cells alone would not able to restore the alloantibody response.…”
Section: The Role Of Cd25 ϩ T Cells In the Regulation Of Alloreactivementioning
confidence: 99%
See 1 more Smart Citation
“…However, humoral tolerance to third-party cells was surprising in that an alloantibody response to private specificities might have been expected. This suggests that humoral tolerance may involve a dominant tolerance mechanism (e.g., Ab feedback through FcR (58) or Treg cells) to public specificities on MHC or additional Ags (57,59) and not simply deletion of donor-specific B cells (60). Although cross-reactive alloimmunity has been well demonstrated, we are not aware of any published data showing that humoral tolerance to one donor can extend to additional donors.…”
Section: Discussionmentioning
confidence: 65%
“…One approach to successfully achieving long-term graft survival in murine cardiac allograft models is with anti-CD154 (MR1) mAb therapy (3)(4)(5)(6)(7)(8). Blocking CD40-CD154 interactions abrogates both naive B cell responses and T cell priming (9).…”
mentioning
confidence: 99%